Interpreting Economic Value Added (EVA) in the Assessment of Financial Performance: A Case Study of Malabo Pharmacy, Parepare - Hidayati, Nurul; Hasan, Hamida (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
This study aims to understand how the concept of Economic Value Added (EVA) is perceived, internalized, and utilized by the owners and managers of Malabo Pharmacy in Parepare in evaluating the financial performance of their business. In contrast to conventional EVA studies that are predominantly quantitative in orientation, this research adopts a descriptive qualitative approach with a case study strategy, thereby emphasizing the exploration of narratives, experiences, and informants’ perspectives on the concept of economic value added. Data were collected through in-depth interviews, documentation review of financial statements, and limited observation of financial management practices within the pharmacy. The data were then analyzed using qualitative procedures, including data reduction, data display, and conclusion drawing. The findings reveal that the introduction of EVA encourages a shift in managerial perspective from a sole focus on accounting profit toward a more comprehensive understanding of performance that incorporates the cost of capital as a critical element of evaluation. The concept of economic value added is not merely interpreted as a computational outcome but also as a measure of the fairness of returns relative to the capital invested and risks borne by the owners. Furthermore, EVA functions as a cognitive framework in structuring operational decisions, assessing the efficiency of resource utilization, and formulating business development strategies. These findings indicate that EVA can be contextually adapted within small-scale healthcare service enterprises such as pharmacies and contributes to enriching the discourse on value creation-based financial performance in small and medium-sized enterprises.